Intervensi Fisioterapi Komunitas Guna Meningkatkan Aktifitas Fungsional Lansia di Desa Malinau Seberang - Sri Sunaringsih Ika Wardojo; Rakhmad Rosadi; Mita Andini Ayu Lestari; Muhammad Ari Azhari (Jurnal Ilmiah Fisioterapi, 2022)
Osteoarthritis is a degenerative joint disease that often affects the elderly due to reduced synovial fluid which functions as a lubricant in the knee joint. Knowledge is needed for the elderly to be more familiar with Osteoarthritis and the symptoms it causes. So that the elderly are more aware of what is happening to their bodies. This case report was conducted at the Elderly Community in Malinau Seberang Village on Jl. PM Dinda Malinau Seberang, Malinau Regency. North Kalimantan. The purpose of this case report is to provide information about osteoarthritis to the elderly community in the village of Malinau Seberang. This research method is counseling and using Pre Test & Post Test Questionnaires to determine the knowledge of the elderly about osteoarthritis and provide a home program in the form of Closed Kinetic Chain Exercise which is given, namely mini squats and quadriceps setting exercise. As many as 13 out of 17 people experienced an increase in the results of the post test that had been carried out.